2020
DOI: 10.1186/s12889-020-8261-4
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among people treated for drug use disorders: a Danish national record-linkage study

Abstract: Background: Substance use disorders are a major risk factor for suicide. However, less is known about specific risk factors for suicide in people with substance use disorders. Methods: This population cohort study assessed suicide among people treated for drug use disorders in Denmark 2000-2010, and described risk factors for completed suicide. Data from 27,942 individuals enrolled in treatment were linked to national registers and matched with controls without drug use disorder and with (n = 138,136) or witho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 54 publications
2
36
1
2
Order By: Relevance
“…Two reviews (18, 57) and a populational study (64) failed to document significant changes in suicidal ideation or behavior in people with MDD after adjusting for confounding factors. Finally, a study by Hesse et al found that compared to the general population, suicide was actually less frequent in individuals with CUD who received treatments in centers for substance use disorders (HR = 0.69) (92). In all, the preponderance of evidence suggests that cannabis use is not associated with suicidal ideation, suicide attempts or completed suicide in MDD.…”
Section: Influence Of Cannabis On the Course And Clinical Presentation Of Depressionmentioning
confidence: 98%
“…Two reviews (18, 57) and a populational study (64) failed to document significant changes in suicidal ideation or behavior in people with MDD after adjusting for confounding factors. Finally, a study by Hesse et al found that compared to the general population, suicide was actually less frequent in individuals with CUD who received treatments in centers for substance use disorders (HR = 0.69) (92). In all, the preponderance of evidence suggests that cannabis use is not associated with suicidal ideation, suicide attempts or completed suicide in MDD.…”
Section: Influence Of Cannabis On the Course And Clinical Presentation Of Depressionmentioning
confidence: 98%
“…As is the trend with gender and suicide in the general population, men who use heroin have higher rates of completed suicide than women, however women who use heroin have higher rates of suicide attempts ( 1 ). With regard to psychopathological symptoms, a diagnosis of major depression, depressive symptoms, anxiety symptoms, post-traumatic stress disorder and antisocial personality disorder have been reported to increase the risk for suicide attempts, and in some instances completed suicide in heroin users ( 6 – 8 , 16 – 19 ). Reports on suicide decedents in the general population show that one-third of people who died by suicide had a general medical illness at the time of death ( 20 ) and people with HIV have approximately a seven times higher risk for suicide than the general population ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, substance use was found to be an independent risk factor for suicide attempt [14]. Substance use disorder (SUD) is considered an important risk factor for suicide, with vulnerable categories identified as younger age, history of psychiatric care, and opioid and alcohol use [15][16][17]. Indeed, substance use, substance intoxication, and pathological substance use have been demonstrated to be positively associated with suicidal behavior [18].…”
Section: Introductionmentioning
confidence: 99%